Security of water supply systems in light of threats in cyberspace - Tchórzewska-Cieślak, Barbara; Rak, Janusz; Rożnowski, Mateusz (Instal, 2024)
Collective water supply systems (CWSS), along with technological progress, are developing towards automatic control of all water production processes. The introduction of modern technologies, including artificial intelligence, is associated with numerous internal and external threats. Collective water supply systems belong to the so-called critical infrastructure, which requires special protection. Attacks on IT systems may result in the leakage of sensitive data and/or the transmission of incorrect data (information) to the system operator. The work presents safety issues in the operation of the water supply system, taking into account the risks in the so-called cyberspace. The collective water supply system has been characterized as a cyber-physical system, developing towards an intelligent technical system. Examples of management levels of CWSS processes using modern IT systems were presented. The authors discussed the concept of IT security. The work also proposes a method of using entropy as a measure of information uncertainty, which can be used in risk analysis in the IT security management process of water supply companies.
Keywords: water supply systems; security; cyberspace